Augmented serum levels of the IGF-I/IGFBP3 ratio in pre-menopausal patients with type I breast cysts - Enriori, Pablo J. (2003)
Gross cystic disease (GCD) is the most common benign breast pathology. Although breast cysts are not considered pre-malignant lesions, an increased risk of breast cancer has been reported for patients with type I cysts (Na(+)/K(+)<3). Furthermore, an augmented IGF-I/IGF-binding protein-3 (IGFBP-3) ratio has been described in breast cancer patients. The objective was to evaluate serum IGF-I and binding protein concentrations of type I and type II cyst patients as compared with healthy women.